Функціональний стан гіпофізарно-тиреоїдної системи у молодших школярів промислових міст Луганської області - Маменко, М. Є. (Clinical Endocrinology and Endocrine Surgery, 2017)
The article deals with some of the results of the regional study of the hypothalamic-thyroid status in junior schoolchildren, which has been conducted in industrial towns of the Luhansk region. We've found out the high level of minimal hypothalamicthyroid dysfunction and hypothyroidism in children in the region of mild iodine deficiency and severe environmental conditions. We've come to the conclusion as for the necessity of an integrate approach to the treatment and preventative measures to improve the iodine status.